Hostel room management with safety using PIC16F877A / Normah Tasiah Zul’aimi - Zul’aimi, Normah Tasiah (2009)
This project paper describes the design of Hostel room controller to ensure that in energy efficient and safe from unwelcome intrusion. The PIC was chosen as to control of the system, it is progressed to use output of motion sensor and a keypad input to ensure that when room is empty, the fan and light will switch off and the door locked. When users enter the door will be via password punched on the keypad. The correct password will open the door and motion sensor will switch on the light and fan. The project construct hardware and software development of the hostel management for full fill comfortable for the student without the key just press the password it control by Peripheral Interface Controller (PIC). This model or prototype hostel room management system design also put the motion sensor to switch on the light and fan control by system from the same user interface. The systems consist of the keypad, liquid crystal display (LCD), motion sensor or motion detector, solenoid, fan and light bulb. LCD will display the character of the welcome note and star (*) for each password enter by user and then the solenoid will open it if the password correct. Motion detector is the action of sensing physical for human body detection in a given area. It can be detected by measuring change in movement of the object in the field of view whether it is 'dark' or 'light' situation [1], The situation when door it's open the motion detector will detect the human motion and then after few second the fan and light will be automatically switch on.